Suitability of Yin Yang 1 transcript and protein levels for biomarker studies in B cell non-Hodgkin lymphoma - Jéssica Arribas Arranz; Dalia Nilufar Winter; Hans Günter Drexler; Sonja Eberth (BMC, 2018)
Abstract Background Yin Yang 1 (YY1) is a transcription factor that plays an important role during all stages of B cell differentiation. Several studies reported upregulation of YY1 in B cell derived lymphoma, indicating that it might act as an oncogene. Furthermore, aberrant YY1 expression has been associated with survival in some entities of B cell non-Hodgkin lymphoma (B-NHL), suggesting that YY1 could be a valuable biomarker in B-NHL. However, studies are controversial and methodologically disparate, partially because some studies are based on transcript levels while others rely on YY1 protein data. Therefore, we aimed to investigate the dependence of YY1 protein levels on YY1 transcription. Methods A panel of human cell lines representing different B-NHL subtypes was used to test for the correlation of YY1 mRNA and protein levels which were determined by quantitative PCR and immunoblotting. To analyze YY1 mRNA and YY1 protein stability cells were treated with actinomycin-D and cycloheximide, respectively. siRNAs were transfected to knockdown YY1. Kaplan-Meier survival analyses were performed with data from published patient cohorts. Pearson's correlation analyses were assessed and statistical power was examined by Student's t-test. Results In the analyzed panel of B-NHL cell lines YY1 transcript levels do not correlate with their cellular protein amounts. YY1 protein levels were unaffected by transient block of transcription or by targeting YY1 mRNA using siRNA. Additionally, global inhibition of translation up to 48 h did not alter protein levels of YY1, indicating that YY1 is a highly stable protein in B-NHL. Furthermore, in a retrospective analysis of two different B-NHL cohorts, YY1 transcript levels had no impact on patients' survival probabilities. Conclusions Our results point out the necessity to focus on YY1 protein expression to understand the potential role of YY1 as an oncogene and to unravel its suitability as clinical biomarker in B-NHL.